A Study on Hysteresis Stiffness Model and Parameter Identification of Harmonic Gear Transmission based on Genetic Characteristic - Linfeng Qiu; Manyi Chen; Gang Song; Jie Zhang; Ran Yang; Han Zhang (Jixie chuandong)
Hysteresis stiffness is an inherent property of harmonic gear drive. In the traditional dynamic modeling of harmonic gear drive，the stiffness is considered as fixed stiffness or piecewise fixed stiffness，which will lead to reduction of the accuracy of the dynamic model. Considering the nonlinear hysteretic characteristics of harmonic drive stiffness， a new hysteretic stiffness model of harmonic gear drive based on genetic characteristics is proposed. The characteristic of the model is that the transmission stiffness is related to the state experienced by the system. Based on the experimental data，particle swarm optimization algorithm is used to identify the model parameters. Taking a certain type of harmonic reducer as the experimental object， the load/unload performance of a harmonic reducer is tested. The fitting results show that the nonlinear hysteretic stiffness model is in good agreement with the experimental data， and the accuracy is greatly improved compared with the traditional model.